2021
DOI: 10.1155/2021/9990338
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG17 Contributes to Proliferation, Migration, and Poor Prognosis of Hepatocellular Carcinoma

Abstract: Long noncoding RNAs (lncRNAs) have been substantially reported to have critical roles in regulating tumorigenesis in recent years. However, the expression pattern and biological function of SNHG17 in hepatocellular carcinoma (HCC) remain unclear. Bioinformatics analysis and qRT-PCR were performed to detect the expression pattern of SNHG17 in HCC tissues, adjacent nontumorous tissues, and cell lines. The effect of SNHG17 on proliferation, migration, and apoptosis of HCC was investigated by knockdown and overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Concerning the studies on the relationship between SNHG17 and tumors, the most significant relationship is the promotion of tumor proliferation, invasion, and metastasis. Several studies have shown that the high-level expression of SNHG7 correlates with lymph node metastasis, distant metastasis, and tumor invasion depth in various tumors ( 19 , 29 , 42 , 44 , 46 ). Spreading to distant organs is recognized to be the most prominent hallmark of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the studies on the relationship between SNHG17 and tumors, the most significant relationship is the promotion of tumor proliferation, invasion, and metastasis. Several studies have shown that the high-level expression of SNHG7 correlates with lymph node metastasis, distant metastasis, and tumor invasion depth in various tumors ( 19 , 29 , 42 , 44 , 46 ). Spreading to distant organs is recognized to be the most prominent hallmark of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, targeting SNHG17 may become a promising strategy for tumor therapy. In addition, SNHG17 can be an independent prognostic factor in hepatocellular carcinoma, renal cell carcinoma, colorectal cancer, gastric cancer, and melanoma ( 26 , 28 , 44 , 46 , 103 ) and a diagnostic predictor in cervical and gastric cancers ( 19 , 42 ) ( Table 1 ). Therefore, SNHG17 is an emerging biomarker for cancer diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy is likely related to a high burden of chronic hepatitis in China [ 58 ]. Several studies previously assessed levels of SNHG17 in human HCCs and adjacent normal tissues via qRT-PCR [ 16 , 59 , 60 ] and found a significant upregulation of SNHG17 in cancer tissues. Ma et al [ 16 ] showed that overexpressed SNHG17 promoted the proliferation, migration, invasion and EMT progression of HCC cells.…”
Section: The Role Of Snhg17 In Cancersmentioning
confidence: 99%
“…LncRNA-hPVT1, AFAP1-AS1, XIST, HOXA cluster antisense RNA 2 (HOXA-AS2), HOST2, and cervical carcinoma high-expressed lncRNA 1 (CCHE1) are examples of lncRNAs that can cause and promote cell proliferation, suppressing apoptosis of HCC cells [ 28 , 176 ]. LncRNA SNHG17 is considerably upregulated in tissues and cell lines of HCC and associated with large tumor size, poor differentiation, and the presence of vascular invasion [ 177 ]. The lncRNA TUG1-miR328-3p-SRSF9 mRNA axis works as a unique ceRNA regulator axis related to HCC malignancies [ 178 ].…”
Section: Lncrnas In Hccmentioning
confidence: 99%